ERS International Congress 2021: highlights from the Paediatric Assembly - Ardura-Garcia, Cristina; Abellan, Alicia; Cuevas-Ocaña, Sara; Freitag, Nadine; Lam, Yin Ting; Makrinioti, Heidi; Slaats, Monique; Storti, Matteo; Williams, Emma E.; Dassios, Theodore; Duijts, Liesbeth; Ersu, Refika H.; et al. (ERJ open research, 2022)
In this review, Early Career Members of the European Respiratory Society (ERS) and the Chairs of the ERS Assembly 7: Paediatrics present the highlights in paediatric respiratory medicine from the ERS International Congress 2021. The eight scientific Groups of this Assembly cover respiratory physiology and sleep, asthma and allergy, cystic fibrosis (CF), respiratory infection and immunology, neonatology and intensive care, respiratory epidemiology, bronchology, and lung and airway development. We here describe new developments in lung function testing and sleep-disordered breathing diagnosis, early life exposures affecting pulmonary function in children and effect of COVID-19 on sleep and lung function. In paediatric asthma, we present the important role of the exposome in asthma development, and how biologics can provide better outcomes. We discuss new methods to assess distal airways in children with CF, as some details remain blind when using the lung clearance index. Moreover, we summarise the new ERS guidelines for bronchiectasis management in children and adolescents. We present interventions to reduce morbidity and monitor pulmonary function in newborns at risk of bronchopulmonary dysplasia and long-term chronic respiratory morbidity of this disease. In respiratory epidemiology, we characterise primary ciliary dyskinesia, identify early life determinants of respiratory health and describe the effect of COVID-19 preventive measures on respiratory symptoms. Also, we describe the epidemiology of interstitial lung diseases, possible consequences of tracheomalacia and a classification of diffuse alveolar haemorrhage in children. Finally, we highlight that the characterisation of genes and pathways involved in the development of a disease is essential to identify new biomarkers and therapeutic targets.